Potencial prebiótico de farinhas de diferentes cultivares de batata-doce (Ipomoea batatas l.) em sistemas de fermentação in vitro - Albuquerque, Thatyane Mariano Rodrigues de (2020)
The intestinal microbiota plays an important role on the physiological and metabolic aspects of the host, being influenced, above all, by dietary components. Prebiotic foods provide necessary substrates to ensure the balance and maintenance of beneficial microorganisms found in the gastrointestinal tract of humans. Sweet potato (Ipomoea batatas L.) is a food of high nutritional value and, due to the amount of different carbohydrates, particularly fiber and starch, can have prebiotic properties. The aim of this study is to evaluate the prebiotic potential of flours obtained from different sweet potato root cultivars in in vitro fermentation systems. The flours were made from the cultivars Rainha-branca (WSPRB), Campina-branca (WSPCB), Vitória (PSPV) and Lagoinha (PSPL), and characterized in terms of their nutritional composition and physical-chemical parameters. Each elaborated flour was submitted or not to an in vitro gastrointestinal digestion in order to evaluate its potential use as a carbon source for the growth of the probiotic strains Lactobacillus acidophilus LA-05, L. casei L-26 and Bifidobacterium animalis subsp. lactis BB-12 using viable cell count assay, as well as assessing changes in the human fecal microbiota using the fluorescence in situ hybridization technique coupled with multiparametric flow cytometry during 48 hours of in vitro fermentation. Scores of prebiotic activity and bacterial metabolic activity (pH values, sugar content and organic acids) were determined in the different culture systems. The results were expressed as the mean ± standard deviation and submitted to Student's t test or analysis of variance (ANOVA), followed by the Tukey test using p ≤0.05. The results obtained for WSPRB, WSPCB, PSPV and PSPL showed high viable cell counts of probiotic strains and induced desirable changes in the bacterial groups forming the intestinal microbiota, such as increase in the relative abundance of the Lactobacillus–Enterococcus and Bifidobacterium populations, and decrease in the relative abundance of Bacteroides–Prevotella, C. histolyticum and E. rectall–C. coccoides during colonic fermentation. Increase in microbial metabolic activity was evidenced by decreasing the pH of the medium, increasing the consumption of sugars (fructose, glucose and maltose) and increasing the amount of different organic acids (formic, lactic, malic, succinic and tartaric) and acids short-chain fatty acids (acetic, butyric and propionic) over time. These findings demonstrate intense bacterial metabolic activity, indicating the ability of WSPRB, WSPCB, PSPV and PSPL to modulate the composition and metabolic activity of the human intestinal microbiota, which must be linked to prebiotic properties. Positive prebiotic activity scores were found in both in vitro fermentations, indicating desirable selective fermentable activity by beneficial bacteria that form the intestinal microbiota in relation to enteric competitors. These results show that flours from different sweet potato root varieties grown in Northeastern Brazil could be considered potential prebiotic ingredients to be used in domestic preparations, as well as functional food formulations or dietary supplements.